Implementation of the 3S Culture (Smile, Greetings, Greetings) in Junior High Schools - Oris Yohanes; Nurfadilah Nurfadilah; Theresia Astita Bura; Oris Kornelis; Amelya Citra (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: School culture plays a crucial role in strengthening students’ character, particularly through the implementation of the 3S culture (Smile, Greetings, and Address), which emphasises politeness and positive communication. Objective: This study aims to analyse the implementation of the 3S culture, the roles of school members, supporting and inhibiting factors, and its impact on students’ character and the overall school climate. Method: The study employs a descriptive qualitative approach, using observation and interviews to obtain in-depth and contextual data. Results: The findings reveal that the 3S culture has been implemented through daily habituation and consistent teacher role-modelling, which have contributed to improvements in students’ discipline, respect, and harmonious interpersonal relationships within the school environment. However, the implementation has not been fully optimal due to inconsistent student participation and insufficient continuous supervision. Conclusion: The 3S culture demonstrates a positive influence in shaping students’ character and fostering a conducive learning environment. Contribution: This study provides a practical contribution by offering a habituation-based model of school culture that can serve as a reference for sustaining character development in educational settings.